System of Social Representations in legal sentences of femicide in Bahia in the years 2020 and 2021 - Feitosa, Ellen Araújo Lima (2024)
Femicide is a complex problem that involves successive forms of violence in emotional relationships, causing significant individual and collective consequences. The objective was to analyze the representational systems present in the discursive repertoires in legal sentences about cases of feminicide in the state of Bahia, in 2020 and 2021. Documentary study of cases reported as feminicide by the Public Ministry in 2020/2021 in Bahia, available at Jusbrasil Platform. 121 documents were found, of which 15 sentences met the inclusion criteria. These were analyzed using the Social Network Analysis approach. The results revealed significant differences in judicial decisions and their reasoning. When comparing the positions between male and female judges, it was noticeable to identify these differences related to gender. Thus, the sentences were mainly anchored in sexist justifications, materialized from the sentences in the representational system. Among these, motivations for crime such as jealousy, feelings of possession and separation.